2014
DOI: 10.1371/journal.pone.0111460
|View full text |Cite
|
Sign up to set email alerts
|

The TLR4 D299G and T399I SNPs Are Constitutively Active to Up-Regulate Expression of Trif-Dependent Genes

Abstract: Dysregulated Toll-Like Receptor (TLR) signalling and genetic polymorphisms in these proteins are linked to many human diseases. We investigated TLR4 functional variants D299G and T399I to assess the impact on LPS-induced responsiveness in comparison to wild-type TLR4. The mechanism by which this occurs in unclear as these SNPs do not lie within the lipid A binding domain or dimerisation sites of the LPS-TLR4/MD2 receptor complexes. Transfection of TLR4D299G, TLR4T399I or TLR4D299G. T399I into HEK cells resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
18
1
2
Order By: Relevance
“…Additionally, they showed that many genes, particularly the TRAM/TRIF signalling pathway constituents, are down‐regulated in unstimulated human monocyte/macrophages from patients with the D299G and T399I SNPs, while upon LPS stimulation these cells display lower NF‐κB levels, higher IFN‐β gene expression levels and overall altered cytokine profiles, compared to the wild‐type receptor. Taken together, these data support that these common TLR‐4 SNPs affect constitutive receptor activity, thus impacting that ability of the host to respond to LPS challenge and a suboptimal immune response to infection .…”
Section: Perspectives and Conclusionmentioning
confidence: 54%
“…Additionally, they showed that many genes, particularly the TRAM/TRIF signalling pathway constituents, are down‐regulated in unstimulated human monocyte/macrophages from patients with the D299G and T399I SNPs, while upon LPS stimulation these cells display lower NF‐κB levels, higher IFN‐β gene expression levels and overall altered cytokine profiles, compared to the wild‐type receptor. Taken together, these data support that these common TLR‐4 SNPs affect constitutive receptor activity, thus impacting that ability of the host to respond to LPS challenge and a suboptimal immune response to infection .…”
Section: Perspectives and Conclusionmentioning
confidence: 54%
“…Yet, not all studies have confirmed the finding. For example, Georgina et al from America reported that Asp299Gly could be considered as a risk factor for non-cardia gastric carcinoma and its precursors (31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals carrying TLR4 Asp299Gly (A896G) and Thr399Ile (C1196T) variants have a higher prevalence of Gram‐negative infections and chronic periodontal disease . These mutations actually lead to constitutive basal activity of the receptor and a dampening of LPS‐inducible inflammatory responses, similar to the phenomenon of tolerisation . In general, SNPs in TLR‐related genes are often associated with hyporesponsiveness to activating stimuli, leading to less efficient immune responses and increased susceptibility to infection.…”
Section: Genetic Links Between Tlrs and Infection Controlmentioning
confidence: 99%